Pengaruh Likuiditas, Profitabilitas, Struktur Modal, Ukuran Perusahaan Dan Kebijakan Dividen Terhadap Nilai Perusahaan Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia - Annisa Nauli Sinaga; Calvin Halim; Sonia Sonia (COSTING : Journal of Economic, Business and Accounting, 2021)
Firm value is one of the criteria used by investors in making decisions to invest in a company where Firm value is often associated with share prices. The purpose of this research is to determine the effect of Capital Structure (DER), Liquidity (QR), Profitability (ROA), Dividends (DPR), and Firm Size (Total Assets) on the Firm Value. This type of research is quantitative descriptive with secondary data, the selection of research samples using purposive sampling techniques, and testing methods with multiple linear regression analysis method. The population in this research were 167 manufacturing companies listed on the IDX during the period 2016 – 2019. Based on the results of the study, it can be concluded that simultaneously the Capital Structure (DER), Liquidity (QR), Profitability (ROA), Dividend (DPR), and Firm Size (total assets) have a simultaneous and positive effect. While partially, only Dividend (DPR) has a positive effect on Firm Value, while Profitability (ROA) have a negative effect on Firm Value; Capital Structure (DER), Liquidity (QR) and Firm Size (Total Assets) have no effect and is insignificant on Firm Value. Keywords : Capital Structure, Liquidity, Profitability, Dividends, Firm Size